POTENSI EKOWISATA BAHARI DI DAERAH PERLINDUNGAN LAUT DESA BAHOI KECAMATAN LIKUPANG BARAT KABUPATEN MINAHASA UTARA - Walandouw, Cindy S.; Andaki, Jardie A.; Kotambunan, Olvie V (AKULTURASI: Jurnal Ilmiah Agrobisnis Perikanan, 2016)
Abstract This study aims to identify the potential for marine ecotourism located in the village of Marine Protected Areas Bahoi Likupang Western District of North Minahasa Regency and determine the contributing factors to the potential of marine ecotourism in the village of Marine Protected Areas Bahoi Likupang Western District of North Minahasa regency. The results based on the analysis of SWOT (Strength, Weakness, Opportunity, Treath) the factor of the power potential of marine ecotourism in protected village Bahoi namely: (1) the existence of mangrove, seagrass and coral reefs that are potentially used as tourist attraction, (2) the naturalness and authenticity of the region DPL Village Bahoi, (3) the appeal and beauty of the sea, (4) government policies through village regulations that favor the development of marine ecotourism, (5) There is a group of business Coastal Village and Group business Ecotourism supporting and regulating the activities of ecotourism development nautical Village Bahoi, (6) cultural attractions of the community as a visitor attraction. (7) The access road is good, (8) Access good and adequate, (9) The availability of human resources as a potential workforce. There is also the disadvantage that there are factors that are still lacking and the promotion of facilities and infrastructures are inadequate as the carrying capacity of marine ecotourism development in the village of Marine Protected Areas Bahoi. Keywords : Potential, Ecotourism, Ecosystem Â  Abstrak Penelitian ini bertujuan untuk mengidentifikasi potensi ekowisata bahari yang terdapat di Daerah Perlindungan Laut Desa Bahoi Kecamatan Likupang Barat Kabupaten Minahasa Utara serta menentukan faktor pendukung terhadap potensi ekowisata bahari di Daerah Perlindungan Laut Desa Bahoi Kecamatan Likupang Barat Kabupaten Minahasa Utara. Hasil penelitian berdasarkan analisis SWOT (Strength, Weakness, Opportunity, Treath) maka faktor kekuatan potensi ekowisata bahari di DPL Desa Bahoi yaitu : (1) keberadaan ekosistem mangrove, lamun dan terumbu karang yang potensial dijadikan obyek wisata, (2) kealamian dan keaslian kawasan DPL Desa Bahoi, (3) daya tarik dan keindahan bawah laut, (4) kebijakan pemerintah lewat peraturan desa yang menguntungkan pengembangan ekowisata bahari, (5) Adanya Kelompok Pengelola Pesisir Desa dan Kelompok Pengelola Ekowisata yang mendukung dan mengatur kegiatan pengembangan ekowisata bahari di Desa Bahoi, (6) Atraksi budaya dari masyarakat sebagai daya tarik pengunjung. (7) Akses jalan yang baik, (8) Akses jaringan yang baik dan memadai, (9) Tersedianya sumberdaya manusia yang berpotensi sebagai tenaga kerja. Adapula terdapat faktor kelemahan yaitu promosi yang masih kurang serta sarana dan prasana yang belum memadai sebagai daya dukung pengembangan ekowisata bahari di DPL Desa Bahoi. Kata Kunci : Potensi, Ekowisata, Ekosistem